2002
DOI: 10.1074/jbc.m204126200
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine to Inosine Editing by ADAR2 Requires Formation of a Ternary Complex on the GluR-B R/G Site

Abstract: RNA editing by members of the ADAR (adenosine deaminase that acts on RNA) enzyme family involves hydrolytic deamination of adenosine to inosine within the context of a double-stranded pre-mRNA substrate. Editing of the human GluR-B transcript is catalyzed by the enzyme ADAR2 at the Q/R and R/G sites. We have established a minimal RNA substrate for editing based on the R/G site and have characterized the interaction of ADAR2 with this RNA by gel shift, kinetic, and crosslinking analyses. Gel shift analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…This is in agreement with the observation in gel mobility assays that are indicative for a stepwise formation of a monomer and then a dimer at an editing site (see Fig. 2C; Jaikaran et al 2002).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is in agreement with the observation in gel mobility assays that are indicative for a stepwise formation of a monomer and then a dimer at an editing site (see Fig. 2C; Jaikaran et al 2002).…”
Section: Discussionsupporting
confidence: 78%
“…As previously seen, the short substrate containing only the R/G stem-loop exhibited two defined complex bands ( Fig. 2C), which have been suggested to represent binding of protein monomers and dimers (Jaikaran et al 2002).…”
Section: Resultsmentioning
confidence: 56%
“…Most of the evidence indicates that the answer is yes. First, mobility shift assays have demonstrated consecutive binding of two ADAR2 monomers to an RNA (Ohman et al 2000;Jaikaran et al 2002). Second, high concentrations of RNA inhibit editing suggesting that excess of RNA leaves no enzymes free in solution for dimerization (Hough and Bass 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism of how the RNA binding facilitates catalysis is still uncertain, but in vitro studies suggest that formation of a ternary complex with two ADAR2 proteins per substrate is required for activity (Jaikaran et al 2002), and purifications of ADAR1 and 2 indicate that they both form homodimers (Cho et al 2003). For the Drosophila ADAR, the N terminus and the first DRBM were shown to be necessary for dimerization and catalytic activity (Gallo et al 2003), while the human ADAR2 does not depend on the N-terminal region for RNA editing (Macbeth et al 2004), suggesting that the ADAR2 dimerization domain differs from that of the Drosophila ADAR.…”
Section: Introductionmentioning
confidence: 99%
“…Since inosine is recognized as guanosine at translation, editing within a coding sequence will often lead to a change in codon usage. Evidence has been found that ADARs form homodimers on dsRNA, a necessary event for editing activity (Jaikaran et al 2002;Cho et al 2003;Gallo et al 2003). ADAR enzymes deaminate adenosines nonselectively within completely base-paired dsRNA that is longer than 50 bp (Nishikura et al 1991;Polson and Bass 1994).…”
Section: Introductionmentioning
confidence: 99%